Identifying the Psychological and Social Determinants of Academic Resilience in Adolescents: A Qualitative Exploration - Rodrigues da Silva, Diana; Wanjiku, Judith (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to explore the psychological and social determinants of academic resilience in adolescents. Methods and Materials: A qualitative descriptive–exploratory design was employed, using purposive sampling to recruit 21 secondary school students aged 14–18 years from various socio-economic backgrounds and school settings in Kenya. Inclusion criteria required participants to have experienced significant academic challenges while demonstrating persistence and adaptability. Data were collected through in-depth semi-structured interviews, guided by an interview protocol addressing psychological resources, social support systems, coping strategies, and environmental influences. Interviews were conducted face-to-face, audio-recorded with consent, and transcribed verbatim. Data collection continued until theoretical saturation was reached. NVivo 14 software was used to manage and code the data, and thematic analysis was applied to identify core themes and subthemes. Findings: Analysis revealed four overarching themes: (1) psychological resources, including positive self-belief, goal orientation, emotional regulation, intrinsic motivation, and adaptability; (2) social support systems, encompassing family encouragement, peer support, teacher mentorship, community involvement, and institutional support; (3) coping strategies and skills, such as problem-solving, time management, help-seeking, stress-relief activities, and resource utilisation; and (4) environmental and contextual factors, including safe learning environments, socio-economic stability, cultural expectations, policy and school structure, exposure to opportunities, technological access, and geographic location. These determinants were found to interact dynamically, fostering sustained engagement and academic persistence. Conclusion: Academic resilience among adolescents is a multifaceted construct shaped by the synergy between individual psychological competencies and robust social and environmental supports.